2009
DOI: 10.1007/s10295-009-0620-1
|View full text |Cite
|
Sign up to set email alerts
|

Lignocellulolytic enzyme activity, substrate utilization, and mushroom yield by Pleurotus ostreatus cultivated on substrate containing anaerobic digester solids

Abstract: Solid waste from anaerobic digestion of litter from the commercial production of broiler chickens has limited use as fertilizer. Its disposal is a major problem for digester operators who are seeking alternative use for anaerobic digester solids, also referred to as solid waste (SW). The use of SW as substrates for the cultivation of Pleurotus ostreatus strain MBFBL400 was investigated. Lignocellulolytic enzymes activity, substrate utilization, and mushroom yield were evaluated in ten different substrate combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
40
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(45 citation statements)
references
References 37 publications
(36 reference statements)
4
40
0
Order By: Relevance
“…This implies that hemicellulose was utilized more than cellulose by P. ostreatus. It has been reported that hemicellulose is preferentially utilized over cellulose during solid state fermentation by P. ostreatus [27,59,60]. Wang et al [61] also reported low degradation of cellulose by P. ostreatus cultivated on spent beer grains.…”
Section: Cellulose and Hemicellulosementioning
confidence: 99%
See 2 more Smart Citations
“…This implies that hemicellulose was utilized more than cellulose by P. ostreatus. It has been reported that hemicellulose is preferentially utilized over cellulose during solid state fermentation by P. ostreatus [27,59,60]. Wang et al [61] also reported low degradation of cellulose by P. ostreatus cultivated on spent beer grains.…”
Section: Cellulose and Hemicellulosementioning
confidence: 99%
“…Tests on the potential use of 3 agricultural wastes for cultivating Pleurotus species [5] indicated that the colonization rate of peanut shell substrates was significantly lower than cotton waste or wheat straw. Reports have shown that P. ostreatus could potentially degrade single or combined lignocellulosic substrates [31,32], however degradation was enhanced in combined substrates [27,33,34]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The residual lignocellulosic substrates can be reused by some microorganisms (Wu et al 2014) or hydrolyzed into the fermentable sugars (Balan et al 2008;Wu et al 2013). Extracellular enzymes from SMC include cellulases, xylanases, and ligninases (Isikhuemhen and Mikiashvilli 2009;MayoloDeloisa et al 2009;Yang et al 2015), the activities and amounts of which depend on the mushroom species and its cultivation conditions. These extracellular enzymes have shown wide applications in the brewing, baking, leather, textile, and saccharification industries (Xin and He 2013;Goncalves et al 2015;Kocabas et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there is also another important reason why fungal is used as starter for organic fertilizer, that is the fungal ability to produce endogenous auxin hormone such as indol acetic acid (IAA) hormone (Ahmad et al 2005). Combination of lignocellulolytic enzyme and IAA hormone will produce organic fertilizer that is nutrition rich and containing high concentration of growth hormone regulator, which is necessary to increase the soil fertility and can accelerate the growth of roots, branches, bars, and leaves (Isikhuemhen and Mikiashvilli 2012 Pseudomonas putida (1.1225 μg mL ) (Levean and Lindow 2004;Ahmad et al 2005). Fungal isolates having high activity of lignocellulolytic enzyme and IAA hormone were characterized by measuring the biomass dry weight at varying temperature and pH.m Cultivation was performed on -1 shaker incubator (72 h, 100 rpm min ) with pH variation from 4.0 to 8.0 (with interval pH 1.0) and temperature variation between 20 °C and 60 °C (with interval temperature 10 °C).…”
mentioning
confidence: 99%